Enlightened Religion From Confessional Churches to Polite Piety in the Dutch Republic - Spaans, Joke; Touber, Jetze (Brill's Studies in Intellectual History, 2019)
This volume widens the scope of research into the relation between religion and Enlightenment. The contributions demonstrate the impact of changing worldviews in a variety of intellectual disciplines and cultural milieus. Readership: Cultural historians, historians of ideas, of philosophy, and of religion, interested in the debate over the place of religion in the late seventeenth and early eighteenth century Dutch Republic. Keywords: controversy literature, epistolary culture, early modern knowledge cultures, Enlightenment encyclopedias, intellectual history, pietism, political theory, Romeijn de Hooghe, theology